A multi-porous nano-carbon / titanium dioxide-based catalytic material and preparation method thereof

The organic titanium source is combined with nanocarbon by solvothermal method to form a structurally stable Ti8O8(OH)4(CO2)12 cluster structure, which solves the problems of complex preparation process and high energy consumption of porous TiO2 materials in the prior art, and realizes the preparation of high-efficiency and low-cost porous nanocarbon/titanium dioxide-based catalytic materials.

CN116493002BActive Publication Date: 2025-04-29CHANGSHA UNIVERSITY OF SCIENCE AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310467060.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-27
Publication Date
2025-04-29
Estimated Expiration
2043-04-27

AI Technical Summary

Technical Problem

In the prior art, the preparation of porous TiO2 materials has problems of high energy consumption and high cost in structural collapse in template methods and electrochemical methods, making it difficult to simplify the process, shorten the reaction time and reduce energy consumption.

Method used

The organic titanium source is combined with nanocarbon by solvothermal method to form a structurally stable Ti8O8(OH)4(CO2)12 cluster structure, and then calcined to form a porous nanocarbon/titanium dioxide-based catalytic material.

Benefits of technology

The preparation of nanocarbon/titanium dioxide-based catalytic materials with high crystallinity, uniform pore channels and stronger thermodynamic stability is achieved, which simplifies the process, reduces energy consumption and cost, and improves catalytic activity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116493002B_ABST
    Figure CN116493002B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of photocatalysis technology, and discloses a multi-porous nano-carbon / titanium dioxide-based catalytic material and a preparation method thereof. The preparation method of the multi-porous nano-carbon / titanium dioxide-based catalytic material comprises the following steps: mixing an organic ligand and an organic solvent to obtain a mixed solution, then adding solid nano-carbon, and dispersing to obtain a nano-carbon dispersion solution; adding an organic titanium source to the nano-carbon dispersion solution, dispersing to obtain a mixed solution, and then performing a solvent thermal reaction to obtain a precursor powder; calcining the precursor powder to obtain a multi-porous nano-carbon / titanium dioxide-based catalytic material with high stability. The method has a simple preparation process, low experimental cost, no need to use special equipment, low energy consumption, easy removal of organic ligands, large-scale preparation, and easy industrial production, providing an effective path for large-scale preparation of photocatalytic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalysis, and in particular to a multi-porous nano-carbon / titanium dioxide-based catalytic material and a preparation method thereof. Background Art

[0002] Titanium dioxide (TiO2) is an important semiconductor photocatalytic material with broad application prospects in sewage treatment, environmental protection, photocatalysts and solar cells. However, pure TiO2 has problems such as wide bandgap, poor light response ability, and high recombination rate of photogenerated electrons and holes in applications, resulting in low visible light utilization and poor photocatalytic efficiency. Therefore, methods such as doping modification, catalyst carrier, noble metal sensitization, semiconductor composite, heterojunction construction, and control of structure and morphology are usually used to improve the utilization rate of TiO2 for sunlight, inhibit the recombination of photogenerated electrons and holes, and obtain TiO2 photocatalytic materials with high photocatalytic activity.

[0003] Studies have shown that preparing porous structures is an effective means to obtain TiO2 photocatalytic materials with high catalytic activity. At present, there are two main methods for preparing porous TiO2 materials: one is to use polymers or inorganic materials as templates (such as epoxy resin macroporous polymers, macroporous SiO2, etc.), or to use colloid particles formed by surfactants as templates; the other is to prepare porous TiO2 materials through electrochemical reactions (such as titanium metal anodization). Both methods have certain limitations. For example, the shape of the template in the template method determines the morphology and structure of the material, and in the process of removing the template, it is easy to cause the product structure to collapse and the pore morphology to be destroyed, reducing the quality of the product; the electrochemical method requires special instruments and equipment, requires additional electricity, and requires additional costs to treat the electrolytic solution, increasing the preparation cost.

[0004] Therefore, it is of great significance to simplify the preparation process, shorten the reaction time, reduce energy consumption, and obtain titanium dioxide-based catalytic materials with high catalytic activity and stable performance. Summary of the invention

[0005] The purpose of the present invention is to provide a multi-porous nano-carbon / titanium dioxide-based catalytic material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a multi-porous nano-carbon / titanium dioxide-based catalytic material, comprising the following steps:

[0008] (1) mixing an organic ligand and an organic solvent to obtain a mixed solution, and then adding solid nanocarbon to disperse and obtain a nanocarbon dispersed solution;

[0009] (2) adding an organic titanium source to the nanocarbon dispersion solution, dispersing to obtain a mixed solution, and then performing a solvothermal reaction to obtain a precursor powder;

[0010] (3) The precursor powder is calcined to obtain a porous nanocarbon / titanium dioxide-based catalytic material.

[0011] Preferably, in the above-mentioned method for preparing a multi-porous nanocarbon / titanium dioxide-based catalytic material, the organic ligand in step (1) is one or both of terephthalic acid and trimesic acid, the solid nanocarbon in step (1) is one or more of graphene oxide, reduced graphene oxide, and carbon nanotubes, and the organic titanium source in step (2) is one or more of butyl titanate, titanium isopropoxide, and titanium butoxide.

[0012] Preferably, in the above-mentioned method for preparing a porous nanocarbon / titanium dioxide-based catalytic material, the mass volume ratio of the organic ligand to the organic solvent in the step (1) is 1.494-2.988 g: 60-120 mL, and the organic solvent in the step (1) is a mixed solution of N,N-dimethylformamide and methanol, and the volume ratio of N,N-dimethylformamide to methanol in the mixed solution is 5:1-9:1.

[0013] Preferably, in the above-mentioned method for preparing a porous nanocarbon / titanium dioxide-based catalytic material, the mass volume ratio of the organic ligand and solid nanocarbon in step (1) to the organic titanium source in step (2) is 1.494-2.988 g: 0.003-0.03 g: 2-10 mL.

[0014] Preferably, in the above-mentioned method for preparing a porous nanocarbon / titanium dioxide-based catalytic material, the time of the solvent thermal reaction in step (2) is 8 to 15 hours, and the temperature of the solvent thermal reaction is 120 to 140°C.

[0015] Preferably, in the above-mentioned method for preparing a porous nanocarbon / titanium dioxide-based catalytic material, after the solvent thermal reaction in step (2) is completed, the following step further includes: filtering and washing the precipitate obtained after the solvent thermal reaction is completed in sequence, and then drying to obtain a precursor powder; the drying temperature is 60 to 80°C, and the drying time is 10 to 20 hours.

[0016] Preferably, in the above-mentioned method for preparing a porous nanocarbon / titanium dioxide-based catalytic material, the calcination conditions in step (3) are: temperature of 400-700° C., time of 80-150 min, and nitrogen atmosphere.

[0017] The present invention also provides a multi-porous nano-carbon / titanium dioxide-based catalytic material prepared by the above-mentioned method for preparing the multi-porous nano-carbon / titanium dioxide-based catalytic material.

[0018] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:

[0019] (1) First, the titanium ions are combined with organic ligands by solvothermal method to form a stable Ti8O8(OH)4(CO2) 12 Cluster structure, the cluster structure continues to aggregate to form a stable porous amorphous precursor, and then the organic matter is oxidized to generate carbon dioxide, Ti8O8(OH)4(CO2) through calcination 12 The porous amorphous precursor generates titanium dioxide, and in this process the structurally stable Ti8O8(OH)4(CO2) 12 The cluster structure still maintains its original structure, forming a highly crystalline multi-porous titanium dioxide-based catalytic material with uniform pores and a simple and adjustable phase composition;

[0020] (2) The nanocarbon structure has excellent mechanical properties and thermal stability. 12 In the process of clustering, nanocarbon structures are easily embedded in Ti8O8(OH)4(CO2) 12 In the cluster structure, it plays a supporting role, effectively preventing the decomposition of organic ligands and Ti8O8(OH)4(CO2) 12 The original structure of the clusters is destroyed, thus forming a nano-carbon / titanium dioxide-based catalytic material with stronger thermodynamic stability, larger specific surface area and uniform pores;

[0021] (3) The present invention has a short reaction time, a simple preparation process, does not require the use of special equipment, is low in cost, and is easy to mass produce; the prepared catalytic material has excellent performance and can be applied to environmental protection fields such as sewage treatment, photodegradation of water, and air purification, and can be industrially produced, providing an effective path for the large-scale preparation of other porous materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required to be used in the description of the embodiments or the prior art are briefly introduced below.

[0023] Figure 1 is a SEM image of the multi-porous nano-carbon / titanium dioxide-based catalyst material in Example 1; wherein a is a cross-sectional SEM image of the multi-porous nano-carbon / titanium dioxide-based catalyst material, and b is a cross-sectional SEM image of the multi-porous nano-carbon / titanium dioxide-based catalyst material;

[0024] Figure 2 is a SEM image of a cross section of the multi-porous nano-carbon / titanium dioxide-based catalytic material in Example 2;

[0025] Figure 3is the XRD spectrum of the multi-porous nano-carbon / titanium dioxide-based catalyst material in Example 3;

[0026] Figure 4 This is a diagram of the photocatalytic performance of the multi-porous nano-carbon / titanium dioxide-based catalytic material in Example 4. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing a multi-porous nano-carbon / titanium dioxide-based catalytic material, comprising the following steps:

[0028] (1) mixing an organic ligand and an organic solvent to obtain a mixed solution, and then adding solid nanocarbon to disperse and obtain a nanocarbon dispersed solution;

[0029] (2) adding an organic titanium source to the nanocarbon dispersion solution, dispersing to obtain a mixed solution, and then performing a solvothermal reaction to obtain a precursor powder;

[0030] (3) The precursor powder is calcined to obtain a porous nanocarbon / titanium dioxide-based catalytic material.

[0031] In the present invention, the organic ligand in step (1) is preferably one or two of terephthalic acid and trimesic acid, more preferably terephthalic acid; the solid nanocarbon in step (1) is preferably one or more of graphene oxide, reduced graphene oxide, and carbon nanotubes, further preferably one or two of graphene oxide and carbon nanotubes, more preferably graphene oxide.

[0032] In the present invention, the mass volume ratio of the organic ligand to the organic solvent in the step (1) is preferably 1.494-2.988 g: 60-120 mL, further preferably 1.55-2.82 g: 65-110 mL, and more preferably 1.8 g: 75 mL; the organic solvent in the step (1) is preferably a mixed solution of N,N-dimethylformamide and methanol, and the volume ratio of N,N-dimethylformamide to methanol in the mixed solution is preferably 5:1-9:1, further preferably 6:1-8:1, and more preferably 7.5:1.

[0033] In the present invention, the mass volume ratio of the organic ligand, solid nanocarbon in step (1) and the organic titanium source in step (2) is preferably 1.494-2.988 g: 0.003-0.03 g: 2-10 mL, further preferably 1.5-2.54 g: 0.0035-0.02 g: 3.5-8 mL, and more preferably 2.2 g: 0.008 g: 4 mL.

[0034] In the present invention, the specific method of dispersing in step (1) is ultrasonic dispersion, and the dispersion time is preferably 15 to 30 minutes, more preferably 15, 18, 20, 22, 25, 28 or 30 minutes, and more preferably 22 or 25 minutes.

[0035] In the present invention, the organic titanium source in step (2) is preferably one or more of butyl titanate, titanium isopropoxide, and titanium butoxide, more preferably one or two of butyl titanate and titanium isopropoxide, and more preferably butyl titanate.

[0036] In the present invention, the specific process of dispersion in step (2) is: stirring for 20 to 40 minutes and then ultrasonically dispersing for 10 to 30 minutes.

[0037] In the present invention, the time of the solvent thermal reaction in step (2) is preferably 8 to 15 hours, more preferably 8, 9, 10, 11, 12, 13 or 15 hours, more preferably 12 or 13 hours; the temperature of the solvent thermal reaction is preferably 120 to 140°C, more preferably 120, 122, 125, 128, 130, 135, 138 or 140°C, more preferably 130 or 135°C.

[0038] In the present invention, after the solvent thermal reaction in step (2) is completed, the process further includes: naturally cooling the precipitate obtained after the solvent thermal reaction to room temperature, filtering and washing in sequence, and then drying to obtain a precursor powder; the drying temperature is preferably 60 to 80°C, more preferably 60, 63, 65, 70, 72, 75 or 80°C, more preferably 75°C; the drying time is preferably 10 to 20h, more preferably 10, 12, 15, 18 or 20h, more preferably 15 or 18h.

[0039] In the present invention, the calcination conditions in step (3) are: the temperature is preferably 400-700°C, more preferably 400, 450, 500, 550, 600, 650 or 700°C, more preferably 600°C; the time is preferably 80-150 min, more preferably 80, 90, 100, 110, 120, 130, 140 or 150 min, more preferably 100 min; the atmosphere is preferably nitrogen.

[0040] The present invention also provides a multi-porous nano-carbon / titanium dioxide-based catalytic material prepared by the above-mentioned method for preparing the multi-porous nano-carbon / titanium dioxide-based catalytic material.

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] Example 1

[0043] (1) dissolving 1.494 g of trimesic acid in 60 mL of a mixed solvent of N,N-dimethylformamide and methanol, wherein the volume ratio of N,N-dimethylformamide to methanol is 9:1; after the trimesic acid is dissolved, adding 0.003 g of graphene oxide powder, and ultrasonically dispersing for 15 min to obtain a graphene oxide dispersion solution;

[0044] (2) Under stirring, 2 mL of butyl titanate was added to the graphene oxide dispersion solution, and the stirring was continued for 20 min, and then ultrasonic dispersion was performed for 10 min to obtain a mixed solution; then the mixed solution was transferred to a reactor with a polytetrafluoroethylene liner, and the reactor was placed in an electric heated blast drying oven at 120° C. for 8 h. After naturally cooling to room temperature, the obtained precipitate was filtered and washed, and then the obtained precipitate was placed in a 60° C. oven for 10 h to obtain a precursor powder;

[0045] (3) The precursor powder is placed in a heat treatment furnace and calcined at 400° C. for 80 min in a nitrogen atmosphere to obtain a porous nanocarbon / titanium dioxide-based catalytic material.

[0046] Figure 1 This is the SEM image of the obtained porous nanocarbon / titanium dioxide-based catalytic material. It can be seen from the image that the surface of the obtained sample presents a pore structure, which indicates that this method successfully prepares a porous nanocarbon / titanium dioxide-based catalytic material.

[0047] Example 2

[0048] (1) 1.822 g of terephthalic acid and trimesic acid were dissolved in 80 mL of a mixed solvent of N,N-dimethylformamide and methanol, wherein the volume ratio of N,N-dimethylformamide to methanol was 6:1; after the terephthalic acid and trimesic acid were dissolved, 0.02 g of carbon nanotube powder was added, and ultrasonic dispersion was performed for 18 min to obtain a carbon nanotube dispersion solution;

[0049] (2) Under stirring, 8 mL of titanium isopropoxide was added to the carbon nanotube dispersion solution, and stirring was continued for 30 min, and then ultrasonic dispersion was performed for 20 min to obtain a mixed solution; then the mixed solution was transferred to a reactor with a polytetrafluoroethylene liner, and the reactor was placed in an electric heated blast drying oven at 130° C. for 12 h. After naturally cooling to room temperature, the obtained precipitate was filtered and washed, and then the obtained precipitate was placed in a 70° C. oven for 15 h to obtain a precursor powder;

[0050] (3) The precursor powder is placed in a heat treatment furnace and calcined at 500° C. for 120 min in a nitrogen atmosphere to obtain a porous nanocarbon / titanium dioxide-based catalytic material.

[0051] Figure 2 This is a SEM image of the cross section of the porous nanocarbon / titanium dioxide-based catalytic material. It can be seen from the image that the sample has obvious pores, and the pores are interconnected.

[0052] Example 3

[0053] (1) dissolving 2.988 g of trimesic acid in 120 mL of a mixed solvent of N,N-dimethylformamide and methanol, wherein the volume ratio of N,N-dimethylformamide to methanol is 5:1; after the trimesic acid is dissolved, adding 0.03 g of reduced graphene oxide powder, and ultrasonically dispersing for 30 min to obtain a reduced graphene oxide dispersion solution;

[0054] (2) Under stirring, 10 mL of titanium butoxide was added to the reduced graphene oxide dispersion solution, and stirring was continued for 40 min, and then ultrasonic dispersion was performed for 30 min to obtain a mixed solution; then the mixed solution was transferred to a reactor with a polytetrafluoroethylene liner, and the reactor was placed in an electric heated blast drying oven at 140° C. for 15 h. After naturally cooling to room temperature, the obtained precipitate was filtered and washed, and then the obtained precipitate was placed in an oven at 80° C. for 20 h to finally obtain a precursor powder;

[0055] (3) The precursor powder is placed in a heat treatment furnace and calcined at 600° C. for 150 min in a nitrogen atmosphere to obtain a porous nanocarbon / titanium dioxide-based catalytic material.

[0056] Figure 3 The XRD diagram of the multi-porous nano-carbon / titanium dioxide-based catalytic material sample obtained above is shown in Figure 1. As can be seen from the figure, the crystal structure of the obtained sample is anatase and rutile mixed phase titanium dioxide.

[0057] Example 4

[0058] (1) 2.580 g of terephthalic acid was dissolved in 100 mL of a mixed solvent of N,N-dimethylformamide and methanol, wherein the volume ratio of N,N-dimethylformamide to methanol was 6:1; after the terephthalic acid was dissolved, 0.01 g of a mixed powder of graphene oxide and carbon nanotubes (the mass ratio of the two was 1:1) was added, and ultrasonic dispersion was performed for 15 min to obtain a graphene oxide dispersion solution;

[0059] (2) Under stirring, 5 mL of titanium isopropoxide was added to the graphene oxide dispersion solution, and stirring was continued for 30 min, and then ultrasonic dispersion was performed for 20 min to obtain a mixed solution; the mixed solution was then transferred to a reactor with a polytetrafluoroethylene liner, and the reactor was placed in an electric heated blast drying oven at 120° C. for 10 h. After naturally cooling to room temperature, the obtained precipitate was filtered and washed, and then the obtained precipitate was placed in an oven at 80° C. for 10 h to finally obtain a precursor powder;

[0060] (3) The precursor powder is placed in a heat treatment furnace and calcined at 700° C. for 80 min in a nitrogen atmosphere to obtain a porous nanocarbon / titanium dioxide-based catalytic material.

[0061] Figure 4 The performance diagram of the above-obtained multi-porous nano-carbon / titanium dioxide-based catalytic material in photocatalytic degradation of Rhodamine B under a 100W high-pressure mercury lamp. It can be seen from the figure that the prepared multi-porous titanium oxide-based catalytic material has a certain photocatalytic degradation ability. After adding graphene oxide, the multi-porous nano-carbon / titanium dioxide-based catalytic material shows better photocatalytic degradation performance. This shows that nano-carbon can effectively improve the photocatalytic activity of multi-porous titanium dioxide and is expected to be applied in actual industry.

[0062] In summary, the present invention uses N,N-dimethylformamide and methanol as solvents, selects organic titanium sources and ligands, and prepares multi-porous nano-carbon / titanium dioxide-based catalytic materials with high catalytic activity. The method has a simple preparation process, readily available raw materials, low cost, and is easy to industrialize.

[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a porous nanocarbon / titanium dioxide-based catalytic material, characterized in that: The following steps are involved: (1) mixing an organic ligand and an organic solvent to obtain a mixed solution, and then adding solid nanocarbon to disperse and obtain a nanocarbon dispersed solution; (2) adding an organic titanium source to the nanocarbon dispersion solution, dispersing to obtain a mixed solution, and then performing a solvothermal reaction to obtain a precursor powder; (3) calcining the precursor powder to obtain a porous nanocarbon / titanium dioxide-based catalytic material; In the step (1), the organic ligand is one or both of terephthalic acid and trimesic acid, in the step (1), the solid nanocarbon is one or both of graphene oxide and reduced graphene oxide, and in the step (2), the organic titanium source is one or more of butyl titanate, titanium isopropoxide, and titanium butoxide; The mass volume ratio of the organic ligand and the solid nanocarbon in step (1) to the organic titanium source in step (2) is 1.494-2.988 g: 0.003-0.03 g: 2-10 mL; The specific method of dispersion in step (1) is ultrasonic dispersion, and the dispersion time is 15 to 28 minutes; The solvent thermal reaction time in step (2) is 8 to 15 hours, and the solvent thermal reaction temperature is 120 to 140° C.; The calcination conditions in step (3) are as follows: temperature of 400-700° C., time of 80-110 min, and nitrogen atmosphere.

2. The method for preparing a porous nanocarbon / titanium dioxide-based catalytic material according to claim 1, characterized in that: The mass volume ratio of the organic ligand to the organic solvent in the step (1) is 1.494-2.988 g: 60-120 mL, and the organic solvent in the step (1) is a mixed solution of N,N-dimethylformamide and methanol, and the volume ratio of N,N-dimethylformamide to methanol in the mixed solution is 5:1-9:

1.

3. The method for preparing the multi-porous nano-carbon / titanium dioxide-based catalytic material according to claim 2, characterized in that: After the solvothermal reaction in step (2) is completed, the method further comprises: filtering and washing the precipitate obtained after the solvothermal reaction is completed in sequence, and then drying to obtain a precursor powder; the drying temperature is 60-80° C., and the drying time is 10-20 hours.

4. The multi-porous nano-carbon / titanium dioxide-based catalytic material obtained by the preparation method of the multi-porous nano-carbon / titanium dioxide-based catalytic material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Preparation method and application of carbon nano tube compound titanium dioxide porous carbon material

    CN109205743A